The 2018 archaeological survey at Tawi Said, Sultanate of Oman - Döpper, Stephanie 1986-; Biezeveld, Irini; Maiorano, Maria Pia; Kluge, Jonas (Archaeopress Publishing, 2023)
"The 2018 archaeological survey at Tawi Said, located on the edge of the Sharqiyah desert in the Sultanate of Oman, yielded close to 8600 artifacts, the majority being pottery sherds. Two significant phases are attested by the survey's finds: the Wadi Suq period (2000-1600 BCE) and the Late Islamic period (1650-1970 CE)."
Keywords: Altertümer; Oman; Archaeological surveying / Oman; Tawi Said Site (Oman); Oman / Antiquities